EVALUATION DE CONNAISSANCES DES FEMMES ENCEINTES ET ALLAINTANTES SUR L’INTERVALLE INTER GENESIQUE INFERIEUR A DEUX ANS. Cas de la Zone de santé de BASOKO du 1er janvier au 30 juin 2019 (RD Congo) - Je t’aime BAFOLA MOTOHIANGENE; Sylvain MOKILIKANDA ISOMOKELE; Emmanuel ELUMBE LIBULA; Jasmes OFUKA LOKOMBA; Salomon OTOWANGE MANDEFU Y; Edouard LOKATUNGA EMALEKE (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
This survey was about the assessment of knowledge of the pregnant and lacting women on the interval inter reproduction lower than two years in Basoko of January 1st to June 30, 2019 in Democratic Republic of Congo. She/it aimed like objective to value the knowledge of the pregnant and nursing women of Basoko on the interval inter reproduction lower than two years. She/it was descriptive to aimed transversal and interested 78 women of 4 areas of health (Ambambe, Libamba, Mambandu and Toyokana) of the Zone of Health of Basoko during the period of survey. The results gotten of our investigation were as: age ≤ 26 years (41%), the domestic profession (62%), the levels of instruction primary and secondary 49% and 38% respectively), the gestated (2 to 4 times): 65% and the ignorance of this approach (85%) were observed more at the mothers. On the other hand, the death (1 to 2 years): 72%, the weak weight (1900 to 2000g) to the birth: 62% of the children presented a curve of growth lower to the normal kept our attention at the children < 2 years. It makes, the sensitization of the pregnant and lacting women in age to procreate on the knowledge of the interval inter reproduction lower than two years home the key of success to reduce the risks bound to this approach.